Acid-responsive aggregated SERS nanoparticles for improved tumor diagnosis. (1st February 2022) - Niu, Xiaoyan; Yu, Licheng; Wang, Xiaohui; Zhang, Zhenjie; Li, Xiaomin; Feng, Xiaoyue; Wang, Wei; Yuan, Zhi
Abstract : The preparation and aggregation process of Au@MCPF NPs. Abstract : Surface-enhanced Raman scattering (SERS) technology has attracted increasing attention in histopathologic examination for tumor diagnosis due to its high resolution and photostability. However, its diagnostic accuracy is inadequate due to its low signal-to-noise ratio (SNR). In order to improve the imaging effect, we constructed a pH-responsive aggregated SERS nanoprobe (Au@MCPF), which was formed via modifying a citraconic anhydride (CA)-linked polyvinyl alcohol (PVA) chain with folic acid (FA)-targeting ability (CC-PVA-FA) and the Raman molecule 4-mercaptobenzoic acid (4-MBA) onto the surface of Au nanoparticles (NPs). In tumor microenvironment, Au@MCPF NPs could actively target the tumor cells, then aggregate in the acidic intracellular environment due to the hydrolysis of the CC-PVA-FA chain and the hydrophobic interaction of 4-MBA, which made the intracellular retention of Au@MCPF NPs increase 2.1-fold compared to monodispersed NPs within 8 h, while the generation of hot spots between the Au NPs enhanced the in vitro Raman imaging SNR of the aggregated NPs 9.2-fold. In addition, the in vivo result showed that the Raman signal of the Au@MCPF NPs in the tumor tissue was 5.2-fold higher than that of isolated NPs, which could improve the imaging contrast. In other words, this pH-responsive aggregated SERS nanoprobe is expected to provide a promising method for the accurate diagnosis of tumors.